2011
DOI: 10.1177/026119291103900212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory and Atrophogenic Effects of Glucocorticoids on Reconstructed Human Skin

Abstract: Topical glucocorticoids (GCs) are extensively used in the treatment of inflammatory skin diseases. However, their long-term use is often accompanied by severe and eventually irreversible adverse effects, with atrophy being the most important limitation. Currently, most non-clinical studies involve animal testing, so the results are not always representative of the situation in humans. The aim of this project was to establish an in vitro test protocol for the evaluation of the anti-inflammatory and atrophic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The effects of glucocorticoids on extracellular matrix components have been studied in monolayer cultures of human dermal fibroblasts by several groups, however, with rather divergent results [1, 28, 33]. In one study, treatment with glucocorticoids for one to five days showed no effect on COL1A1 and COL3A1 mRNA expression while HAS2 mRNA expression and HA production were significantly suppressed [1].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of glucocorticoids on extracellular matrix components have been studied in monolayer cultures of human dermal fibroblasts by several groups, however, with rather divergent results [1, 28, 33]. In one study, treatment with glucocorticoids for one to five days showed no effect on COL1A1 and COL3A1 mRNA expression while HAS2 mRNA expression and HA production were significantly suppressed [1].…”
Section: Discussionmentioning
confidence: 99%
“…During the last 10 years, in vitro skin models have emerged as valuable tools for skin absorption studies, and have proved suitable for drug efficiency testing as demonstrated with glucocorticoid studies [25,26]. Hence, to evaluate the biocompatibility and efficiency of DXM loaded CMS nanocarriers in a more complex system, an inflammatory skin disease model was established.…”
Section: Establishment Of An Inflammatory Skin Modelmentioning
confidence: 99%
“…Rodent skin however demonstrates major anatomical and physiological differences relative to human skin, something that skin models aim to overcome [19][20][21]. Reconstructed human skin has been used to model atopic dermatitis [22], ichthyosis vulgaris [23] and non-melanoma skin cancer in vitro [24], and to assess nanoparticle-mediated delivery [12] and therapeutic efficacies [25,26] .…”
Section: Introductionmentioning
confidence: 99%
“…Primary cultures of normal human dermal fibroblasts were isolated from human juvenile foreskin and cultured as described [21,22]. To reduce donor-specific properties, cells were pooled from at least three donors.…”
Section: Cell Cultures and Stimulimentioning
confidence: 99%
“…Primers (synthesized by TIB Molbiol, Berlin, Germany) with the following sequences were used: COL1A1, COL3A1, HMBS, IL-8, MMP1, TLR1-10 and YWHAZ as published previously [21,23]; ACTA, 5′-TGGGCTCTGTAAGGCCGGCT-3′ and 5′-TCACCC CCTGATGTCTGGGACG-3′; IFN-α, 5′-GTGAGGAAATACTTCCAAAGAATC AC-3′ and 5′-TCTCATGATTTCTGCTCTGACAA-3′; IFN-β, 5′-CAGCAATTTT CAGTGTCAGAAGC-3′ and 5′-TCATCCTGTCCTTGAGGCAGT-3′; IL-1α, 5′-CGCCAATGACTCAGAGGAAGA-3′ and 5′-AGGGCGTCATTCAGGATGAA-3′; IL-1β, 5′-TGGAGCAACAAGTGGTGT-3′ and 5′-TTGGGATCTACACTCT CCAGC-3′; IL-6, 5′-CACAGACAGCCACTCACCTC-3′ and 5′-TTTTCTGCCA GTGCCTCTTT-3′; S1PR1, 5′-CACCGTGCTGCCGCTCTACC-3′ and 5′-GCAG CGCCAGCGACTTCTCA-3′; S1PR2, 5′-GCGCCATTGTGGTGGAAAA-3′ and 5′-CATTGCCGAGTGGAACTTGCT-3′; S1PR3, 5′-GGTGATTGTGGTGAGC GTGTT-3′ and 5′-AGGCCACATCAATGAGGAAGA-3′; S1PR4, 5′-GTGGTG CTGGAGAACTTGCT-3′ and 5′-GGTCACTCAGCGTGATGTTC-3′; S1PR5, 5′-GCTTGCTCCACTGTCTTGC-3′ and 5′-GCGCGTAGAGTGCACAGA-3′; TNF, 5′-CCCAGGGACCTCTCTCTAATCA-3′ and 5′-GCTACAGGCTTGTCAC TCGG-3′. Fold difference in gene expression was normalized to the housekeeping genes, HMBS and YWHAZ, which showed the most constant level of expression in preliminary investigations in which four different housekeeping genes (i.e.…”
Section: Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%